Onda J prominente en un paciente con hipotermia y shock medular: Onda de Osborn - Luzuriaga Navas, Juan A.; Navia Intriago, Otilia L.; Puga Bravo, Marcelo V.; Gallardo Medina, Yisel (CorSalud, 2018)
Onda J prominente en un paciente con hipotermia y shock medular: Onda de Osborn